The role of mental accounting in risk-taking and spending: a meta-analysis of the house-money effect - Dan, Kasumi (Frontiers in Psychology, 2025)
IntroductionThis study systematically analyzes the house-money effect, a phenomenon in which people become more financially risk-taking and wasteful after receiving unexpected income. It aims to identify the general tendencies and factors that influence this effect, because the results reported in previous studies are inconsistent.MethodA total of 36 eligible studies with 57 continuous and 18 binary outcome effect sizes were included in this meta-analysis. A random-effects model was used to pool the effect sizes.ResultsA low-to-moderate house-money effect (g = 0.37, rr = 1.33) was confirmed. However, high heterogeneity was observed, and the strength of the house-money effect varied widely, depending on the situation. The subgroup and meta-regression analyses revealed several moderators. While a strong effect was observed in the controlled experimental environment, the effect was weakened when it was closer to a real-world environment. For continuous outcomes, the effect was particularly pronounced in students and Asian regions, and the effect size decreased as the publication year increased, suggesting the limited universality of the house-money effect. In the publication-bias analysis, a slight bias was detected using multiple methods.DiscussionThis suggests that the true effect size may be smaller, supporting the theory that the house-money effect is reproducible only under certain conditions.